Moj cudowny bajkowy swiat - Grabianski, Janusz; Hauff, Wilhelm, 1802-1827.; Andersen, H. C. (Hans Christian), 1805-1875.; Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859. (Zielona Gora : Wydawnictwo E. Jarmolkiewicz, 1994)
A selection of fairy tales from Andersen, Brothers Grimm, Hauff and others about the world of animals. Ages 6-10.
Fairy tales by Hans Christian Andersen, Brothers Grimm, and Wilhelm Hauff.